Effects of water content and chain length of n-alkane on the interaction enthalpy between the droplets in water/sodium bis(2-ethylhexyl)-sulfosuccinate/n-alkane microemulsions. Issue 14 (14th April 2015) - Fan, Dashuang; Zheng, Peizhu; Ma, Yuanming; Yin, Tianxiang; Zhao, Jihua; Shen, Weiguo
<x xml:space="preserve">Abstract</x> The interaction enthalpies between microemulsions droplets depends on the water contents ω0 and chain lengths n of n-alkane. The entropy effect plays an important role in microemulsion systems.